Analysis Performance of Tax Effort and Privilege Funds Influencing Economy of Special Region of Yogyakarta in 2014-2019 - Gilang Pangestu, Yustiko Arvandero (Universitas Negeri Semarang, 2022)
Privileges funds is a fund originating from the State Revenue and Expenditure Budget which is allocated to fund special authorities of the Special Region of Yogyakarta. This study aims to determine the effect of privileges funds on the economy in the Special Region of Yogyakarta during 2014-2019 as well as to determine the condition of the tax business during the privilege period. The method used in this research is quantitative by using descriptive analysis to analyze data development and regression analysis to analyze the effect of privilege funds on selected indicators. The data used in this research is panel data consisting of time series data for 2014-2019 and cross-section data of five districts / cities in DIY. The dependent variable used in this study are poverty percentage, Gross Regional Domestic Product per capita and Gross Regional Domestic Product (GRDP), while the independent variable used in this study is privilege funds. The results of this research indicate that: Tax effort during the Privileges Law era showed an upward trend, the privileges funds has a negative and significant effect on the poverty percentage, the privileges funds has a positive and significant effect on GRDP per capita and the privilegs funds has a positive and significant effect on the GRDP. This study concludes that the role of privilege funds needs to be increase in order to maximize returns to the economy.